Nitrogen concentration affects amphotericin B and fluconazole tolerance of pathogenic cryptococci. Issue 2 (19th February 2020) - Bosch, Caylin; Toplis, Barbra; Vreulink, Jo-Marie; Volschenk, Heinrich; Botha, Alfred
ABSTRACT: Environmental stress often causes phenotypic changes among pathogenic cryptococci, such as altered antifungal susceptibility, changes in capsule and melanin formation, as well as altered levels of the membrane sterol and antifungal target, ergosterol. We therefore hypothesised that nitrogen limitation, a prevalent environmental stress in the natural habitat of these yeasts, might affect virulence and antifungal susceptibility. We tested the effect of different nitrogen concentrations on capsule, melanin and ergosterol biosynthesis, as well as amphotericin B (AmB) and fluconazole (FLU) susceptibility. This was achieved by culturing cryptococcal strains representing Cryptococcus neoformans and Cryptococcus gattii in media with high (0.53 g/l), control (0.42 g/l) and low (0.21 g/l) NH4 Cl concentrations. India ink staining was used to determine capsule thickness microscopically, while melanin and ergosterol content were determined spectrophotometrically. We found that lower nitrogen concentrations enhanced both ergosterol and capsule biosynthesis, while a variable effect was observed on melanisation. Evaluation of drug tolerance using time-kill methodology, as well as tests for FLU heteroresistance, revealed that the low nitrogen cultures had the highest survival percentages in the presence of both AmB and FLU, and showed the highest frequency of FLU heteroresistance, suggesting that nitrogen concentration may indeed influence drug tolerance. Abstract : Nitrogen concentration affects the virulence factors and antifungal susceptibility of pathogenic cryptococci.